EVALUATION OF EQUIPMENT OF STOPS OF URBAN BUS TRANSPORT IN NITRA (Perner's Contacts, 2013)
The paper deals with the evaluation of equipment of the bus stops that are served by lines of public passenger transport in Nitra. According to the number of lines were the bus stops divided into five categories. The equipment was evaluated based on the selected variables; what should prove a hypothesis that equipment of the stops proportionally increases in accordance with the number of served lines.